2018
DOI: 10.1177/1937586718800481
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Spatial Design on Team Communication in Hospital Emergency Departments

Abstract: Objective: To identify spatial design factors that influence informal interprofessional team-based communication within hospital emergency departments (EDs). Background: Effective team communication in EDs is critical for interprofessional collaborative care and prevention of serious errors due to miscommunication. Limited evidence exists about how informal communication in EDs is shaped by the physical workspace and how workplace design principles can improve the quality of ED team communication. Method: Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…The prescription “creating spaces to facilitate collaborative work,” mentioned by 16 papers, is aligned to the growing need for multidisciplinary care (Lin et al, 2016; Waggener et al, 2021). The literature indicates that healthcare facilities should provide proper spaces for information exchange amongst staff members (Naccarella et al, 2019). Open rooms are more conducive to teamwork since they support social interaction and face-to-face communication (Fay et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prescription “creating spaces to facilitate collaborative work,” mentioned by 16 papers, is aligned to the growing need for multidisciplinary care (Lin et al, 2016; Waggener et al, 2021). The literature indicates that healthcare facilities should provide proper spaces for information exchange amongst staff members (Naccarella et al, 2019). Open rooms are more conducive to teamwork since they support social interaction and face-to-face communication (Fay et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This design principle was the most cited (35 out of the 43 papers) and encompasses three design prescriptions and 16 examples (Figure 3). The most cited design prescription (25) in this group was to "ensure patient privacy without hindering visibility" (Naccarella et al, 2019). An implementation example is the design of a zone outside the patient room that allows visibility to the inside, making it possible the visual monitoring of the patient while avoiding constant entries in the patient room (Rich & Day, 2008).…”
Section: Meta-principle 1: Supporting Visibility Of Processes and Out...mentioning
confidence: 99%
“…The critical features that need to be looked into are the spatial planning and design that require different measurements, which will serve as an essential daily role, mainly to transport equipment and supplies for overall design (Shan & Verderber, 2016). Prior studies have noted that having proper spatial planning and design will indirectly resolve the current issue before hospitals with complex building planning and poor spatial wayfinding either internally or externally (Ulrich et al, 2004;Naccarella et al , 2018). In the studies done by Capolongo (2016), he stated the hospital design should include a specific requirement in the planning and design components that can accommodate the sense of isolation and disorientation to ease patients' concerns and help their recovery journey.…”
Section: Hospital Planning and Designmentioning
confidence: 99%
“…While enclosed layouts have commonly been examined in the ICU or commercial office spaces, it is unheard of in emergency department (ED) practice (Calleja & Forrest, 2011;Wears et al, 2004) since most EDs see virtue in openplan workstations as they provide increased visibility, greater opportunities for frequent interactions, and high collaboration between team members (Gharaveis et al, 2018(Gharaveis et al, , 2020Naccarella et al, 2018;Zamani, 2018). The physical proximity and colocation of clinicians including physicians, physician assistants, and nurses are associated with improved clinician perceptions of teamwork and collaboration (Weaver et al, 2017).…”
mentioning
confidence: 99%
“…The researchers recorded reduced interruptions from 1.4 interruptions/min in an openplan medication station in a pediatric acute ward to 0.27 after a 24 00 partition was placed at the medication station (Colligan et al, 2012). A qualitative study in the ED also reported that ED staff (nurses and physicians) preferred workspaces that provided spatial transparency, that is, visibility and connectedness to the unit to facilitate awareness and positive interactions, but at the same time maintained visual separation and/or acoustic privacy from patients and other staff members (Naccarella et al, 2018). While most studies have examined the needs of ED staff during a regular shift, no study has considered the specific needs of a conducting complex and critical tasks like handoffs.…”
mentioning
confidence: 99%